ARCHETYPE OF GREAT MOTHER IN VASYL STEFANYK’S EPISTOLARY - Ільків, А. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The archetype of Great Mother in V. Stefanyk’s epistolary works on the basis of archetype analysis is researched in the article. The analysis of epistolary texts has allowed us to determine that a mother was the bearer of certain primitive knowledge, folk faith and customs for the writer. Strong father’s will in V. Stefanyk’s epistolary is in contrast to full idyll with a mother as the closest person. The author of the letters often correlates the mother’s image with a certain religious canon, accompanying it with a certain ritual that is one of the attributive features of archetype as a certain mental constant.